Productive Fandom : Intermediality and Affective Reception in Fan Cultures - Lamerichs, Nicolle (Transmedia (Amsterdam, Netherlands), 2020)
To dismantle negative stereotypes of fans, this book offers a media ethnography of the digital culture, conventions, and urban spaces associated with fandoms, arguing that fandom is an area of productive, creative, and subversive value. By examining the fandoms of Sherlock, Glee, Firefly, and other popular television-based franchises, the author appeals to fans and scholars alike in her empirically grounded methodology and insightful analysis of production hierarchies, gender, sexuality, play, and affect.